Food and Beverage Promotion Strategy in Efforts to Attract Hotel Guests (Case Study on Hotel Horison and Prime Hotel Kualanamu) - Edy Erianto (Akademi Pariwisata Darma Agung, 2022)
This study aims to find out what are the forms of Food and Beverage Promotion strategies at Horison Kualanamu Hotel and Prime Hotel Kualanamu Medan in an effort to attract hotel guests, and the success rate of the Food and Beverage Promotion strategy in an effort to attract hotel guests. This research is a descriptive research with a qualitative approach. Data collection techniques using observation, interviews, questionnaires, and documentation. The data analysis technique uses data collection, data reduction, data presentation and drawing conclusions. The results showed that the Food and Beverage Promotion Strategy of Horison Kualanamu Hotel and Prime Hotel Kualanamu in an effort to attract hotel guests was in line with the promotion mix theory according to Philip Kotler, namely firstly Advertising, namely at this stage Hotel Horison Kualanamu and Prime Hotel Kualanamu advertised their products through print media. , electronic media and social media or the internet.